Study Protocol of SURVIVE HERoes (NCT06643585): Trastuzumab Deruxtecan for molecular relapse in HER2+/ Low early breast cancer with ctDNA positivity after primary therapy - Kerstin Pfister; Thomas W. P. Friedl; Andreas Hartkopf; Franziska Mergel; Sophia Huesmann; Forca Mehmeti; Henning Schäffler; Angelina Fink; Tatjana Braun; Sabine Heublein; Lisa Wiesmüller; Klaus Pantel; et al. (PLoS ONE, 2025)
Background Current evidence on circulating tumor DNA (ctDNA) in the adjuvant setting of early breast cancer (eBC) confirms its high prognostic value. CtDNA-positive patients without radiographic signs of relapse show reduced disease-free and overall survival. Secondary adjuvant treatment intervention studies represent a new appealing therapeutic option. Methods We present SURVIVE HERoes , a phase III randomized clinical trial of the potent antibody-drug conjugate trastuzumab deruxtecan versus standard of care (SoC) in patients with HER2 positive or HER2 low eBC and molecular residual or recurrent disease (ctDNA positive, cM0) after primary therapy. The primary endpoint is the ctDNA clearance rate after 12 months of therapeutic intervention. A total of 180 study participants will be enrolled and randomized in a 2:1 ratio to receive trastuzumab deruxtecan or SoC therapy. The trial is accompanied by an extensive translational research project. Discussion Treating ctDNA positive patients without radiographic signs of recurrence is a novel approach. If SURVIVE HERoes and similar studies targeting MRD will be positive, this may lead the way to a new molecular understanding of breast cancer stages and individualized therapy and may open a new therapeutic window for cure.